Factors affecting the intention to use mobile commerce in Malaysia: an integration of TAM and IS success model - Barry, Moussa; Haque, A. K. M. Ahasanul; Jan, Muhammad Tahir (Human Resource Management Academic Research Society (HRMARS), 2024)
Abstract Mobile commerce transactions adoption among consumers in Malaysia has become a major challenge for mobile commerce providers. This paper aims to determine the factors affecting the intention to use mobile commerce by integrating the Technology Acceptance Model and the updated IS Success Model. A non-probability convenience sampling is employed, collecting 395 questionnaires from Klang Valley residents of Malaysia. A two-stage structural equation modeling is employed to test the hypotheses. The findings indicate that system quality, service quality, and perceived enjoyment significantly affect the intention to use mobile commerce. However, the findings further revealed that information quality, perceived ease of use, and perceived usefulness do not significantly influence the intention to use mobile commerce in Malaysia. These findings will benefit mobile commerce providers and businesses aiming to improve the acceptance of mobile commerce transactions in Malaysia. However, this study is valuable for academicians, researchers, policymakers, and practitioners.